(In)credibly queer? Assessments of asylum claims based on sexual orientation - Selim, Hedayat (Legal and criminological psychology, 2025)
Purpose Queer asylum-seekers should be given an opportunity to have their claim evaluated in a fair and unbiased manner. Despite this, research shows they risk having their claims rejected based on stereotypes about sexual minorities. In the present study, we investigated how the Finnish Immigration Service evaluated credibility in asylum claims lodged by sexual minorities. Methods We analysed 68 negative asylum decisions to assess the arguments made to reject the asylum claim. To do this, we developed a detailed coding scheme to investigate the specific themes and credibility indicators cited in the asylum decisions. Results We found that the asylum claims were most often rejected because the applicant's account of their sexual orientation was not found to be sufficiently detailed, consistent, or plausible. Officials appeared to hold assumptions around sexual identity development and interpersonal relationships that are partially unsupported by established psychological science. Conclusions Assessments of SOGI claims would benefit from a greater consideration of the factors affecting queer asylum applicants' ability to describe their claims, including cross-cultural differences in understandings of sexuality, variability in human behaviour, and practical barriers within the asylum procedure.